2013
DOI: 10.1371/journal.ppat.1003407
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Induces Interleukin-1β Expression: Paracrine Macrophage Epithelial Signaling Controls M. tuberculosis Infection

Abstract: Although vitamin D deficiency is a common feature among patients presenting with active tuberculosis, the full scope of vitamin D action during Mycobacterium tuberculosis (Mtb) infection is poorly understood. As macrophages are the primary site of Mtb infection and are sites of vitamin D signaling, we have used these cells to understand the molecular mechanisms underlying modulation of the immune response by the hormonal form of vitamin D, 1,25-dihydroxyvitamin D (1,25D). We found that the virulent Mtb strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(195 citation statements)
references
References 62 publications
12
176
1
6
Order By: Relevance
“…Previous studies showed that IL1B is also induced by M. tuberculosis infection of primary human macrophages (25), a result that we confirmed in this study (Supplemental Fig. 2H).…”
Section: Engagement Of Ahr Signaling During M Tuberculosis Infectionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies showed that IL1B is also induced by M. tuberculosis infection of primary human macrophages (25), a result that we confirmed in this study (Supplemental Fig. 2H).…”
Section: Engagement Of Ahr Signaling During M Tuberculosis Infectionsupporting
confidence: 91%
“…Analysis of the microarray data revealed that AHR, ARNT, and RELB transcripts were well expressed in both uninfected and infected cells (25). Expression of AHR and RELB in THP-1 cells was enhanced modestly (1.5-2-fold) and 3-4-fold, respectively, after 24 h of infection with either H37Ra or H37Rv, whereas that of ARNT was slightly inhibited (25) (Supplemental Fig.…”
Section: Engagement Of Ahr Signaling During M Tuberculosis Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of 1,25-dihydroxyvitamin D 3 is further increased by interferon γ. In addition to cathelicidin and B-defensin, 1,25-dihydroxyvitamin D 3 induces other important antimicrobial factors, including reactive oxygen species, nitric oxide synthase and active form of interleukin-1β that trigger the beginning of inflammation cascade (Verway et al 2013).…”
Section: Introductionmentioning
confidence: 99%